Uncovering the connection of cancel culture and the internet - Ulnagan, Rasabelle; Viernes, Glaiza; Delos Reyes, Denielle Erika; Lazatin, Kristine Joyce; Alipio, Rey Anne; Mendoza, Julie Ann; Balisi, Alva Mia; Ignacio, Gina Rose; Fernandez, Rosalinda; Pascua, Christian Paul (International Journal of Arts, Sciences and Education, 2022)
ABSTRACT: This study aims to unveil the relationship between cancel culture and the internet, to identify the causes and factors of its occurrence. A descriptive research design was adopted. A case study of the cancellation of the different social media personalities of the country the Gonzaga sisters, Buknoy Glamurr, President Rodrigo Duterte, and BryanBoy was also conducted to identify the factors of the emergence of cancel culture. The findings of the study revealed that cancel culture happens for several reasons. The reasons are as follows: (1) varying political views and perspectives, (2) misbehavior, (3) different religious beliefs, (4) violations of human rights. This study gives an exemplary contribution in uncovering the connection between cancel culture and the internet. Keywords: Cancel culture, the internet, social media.